Strategi Pengembangan Usaha Perbenihan Padi Bersertifikat di Subak Guama, Kecamatan Marga, Kabupaten Tabanan - Laksmi, Ni Made Ayu Citra; Windia, Wayan; Suamba, Ketut (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2017)
ABSTRACT Business Development Strategy Certified Rice Seed On Subak Guama, Marga District, Tabanan Regency The increasing rate of population growth led to increased demand for food. In order to achieve food security, the use of certified seeds is one of the factors that influence the improvement of yield and quality of production. Attempt to capture these opportunities, Subak Guama need to make strategic business development of certified rice seed. The purpose of research is to investigate alternative strategies and priorities appropriate strategies run by Subak Guama in the development of certified rice seed business. The research location was at Subak Guama. Respondents were selected purposively regarding their expertise and knowledge of the research. Primary data were collected focus group discussions, surveys, and in-depth interviews. Secondary data were collected from publications. Formulation of alternative strategies and priority strategies using SWOT matrix analysis and analysis QSPM. The results show alternative strategies of business development certified rice seed include: 1) expand market share in order to meet the potential needs of seeds, 2) the formation of youth groups farmer, 3) improving the quality of human resources, 4) empowerment of farmers through the capital strengthening farming 5) integrated pest and disease control, and 6) optimization of the certified rice seed business. The result also shows that the priority strategy selected is capital strengthening farming. In supporting the development of business certified rice seed, members of Subak Guama is expected to strengthen the capital to apply for credit farming through financial institutions/banks so as to increase production and develop products seed varieties vary, increase access to a wider market so as to maintain its market position has been achieved, as well as more effective cooperation between farmers with KUAT Subak Guama. Keywords: SWOT, QSPM, Rice Seed, Subak